2022
DOI: 10.3390/w14030429
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Freshwater Discharge and Wind Forcing on the Dispersal of River Plumes Using a Three-Dimensional Circulation Model

Abstract: Tidal estuaries provide crucial pathways for contaminant transport. The salinity levels in estuaries and coasts are conserved substances that function as natural tracers to easily understand the offshore transport of substances that are subject to environmental factors. A three-dimensional (3D) circulation and mass transport model were utilized to delineate the salinity plume in a tidal estuary and continental shelf. The numerical modeling results were compared with the tidal amplitudes and phases, velocities,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“…Jurisa and Chant (2013) show that the width of the river plume is proportional to the river discharge. Plume areas have a linear relationship with freshwater discharge (Liu et al., 2022). The offshore velocities are larger at the estuary mouth, due to the larger barotropic pressure gradient in this area, which is the same as the results by Gong et al.…”
Section: Resultsmentioning
confidence: 99%
“…Jurisa and Chant (2013) show that the width of the river plume is proportional to the river discharge. Plume areas have a linear relationship with freshwater discharge (Liu et al., 2022). The offshore velocities are larger at the estuary mouth, due to the larger barotropic pressure gradient in this area, which is the same as the results by Gong et al.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the grain‐size distribution of the bedload and bed material were divided into nine size ranges, with the median of each range used in the calculations (Figure 6c). The thickness of the movable layer of the bed was set at 10 m, as recommend by Liu and Huang (2003) based on physical model. The Min River was set to have no bedload supply because the upstream supply is trapped by the Zipingpu Reservoir and we assume that the armour layer of the Min within the Dujiangyan reach is immobile and does not supply sediment to the bedload.…”
Section: Methodsmentioning
confidence: 99%
“…Guo and Zhang (1993) conducted a flume study and reported that the sediment trapping effect of the Zipingpu Reservoir had led to more severe erosion and instability of the Fish Mouth Levee and the Inner River, which required protection. Utilising a downscaled physical model, Liu and Huang (2003) suggested that the long‐term scour depth in the Dujiangyan reach due to the operation of the Zipingpu Reservoir would reach 2 m, with the bed being generally stable following this downcutting. With the regulation of the reservoir, the flow and bedload transport can be redirected to the Outer River, thereby reducing the negative impacts of floods on the Dujiangyan Irrigation Project.…”
Section: Introductionmentioning
confidence: 99%